Technical acceptance assurance limit of iflâ¢ pipelines - Albarody, T.M.B. (Asian Research Publishing Network, 2016)
With a worldwide aging pipeline infrastructure and increasing economic and regulatory constraints for pipeline operators, pipeline integrity issues need to be solved. While pipeline regulations not only demand inspections or monitoring of structural integrity at certain intervals, but a continuous process of verification of pipeline integrity and fitness-for-purpose. In-Field Linear Hose (IFL) offer complemented solution for both maximizing pipeline integrity preventing; corrosion, wear, leakage etc. as well as, a health monitoring tool. IFL has short rehabilitation times and rapid recommissioning, and thus represents not only an inexpensive alternative to open rehabilitation, but also a high-quality method for the renewal of pressure petroleum pipes with an anti-corroded solution. Although, IFL structure can be coiled or uncoiled several times, it embedded optical fibre for health monitoring tool assessing pipeline integrity by inspecting the pipe corrosion, metal loss, deformations, and position. Technical Acceptance Assurance for IFLâ¢ over its 20 years of design life are key deliverables of this study. Whereas, IFL failure mode is typically caused by a succession of defects or degradation that leads to loss of structural integrity. IFL Collapse, Burst, Tensile failure, Torsional failure, Fatigue failure, and Erosion are failure mechanisms expected cause potential IFL failure and need to scrutinize. This paper focuses on wrinkling of IFL under verities loading, deformation and its interaction with the outer pipe. Stresses and strains will scrutinized throughout the deformation stage, detecting possible detachment of the liner from the outer pipe and minimum loads induce wrinkles. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.